Traje mirim: reflexões do processo de criação dos trajes da temática Lendas Amazônicas na quadrilha roceiros da colônia do município de Marituba / PA - LIMA, Flávia de Jesus dos Santos de (2022)
The process of creating the costumes of the junior quadrille Roceiros da Colônia, from Marituba-PA, specifically the theme Amazon Legends, presented in 2014, is closely linked to my practice of drawing, which is why I was asked by the gang in order to meeting the need to create models of June clothes to dress the group, a practice that leveraged my growth as an artist, as well as closer relationships with the people who make the Roceiros da Colônia gang happen. The general objective is to reflect on the process of creation of elaborate costumes, which begin a priori in the design, which shows the Junino group as a reference to show the backstage of this construction of costumes. This is an ethnographic field research that addresses information / knowledge about the preparation of gang costumes, enriched by the drawing records, images, testimonials of the experiences of the gangs involved, who experience the popular culture of June, and exposes the artist's work. designer in relation to the importance of drawing and costume for the June manifestation as a complement of the rustic character to the proposed theme. The main references of this research are: Angrosino (2009), Lakatos and Marconi (2007) on ethnographic method, Bião (2007) and Cascudo (1998) on popular culture, Muniz (2004), Souza and Ferraz (2013), Abling and Maggio (2014) on costume design, Harrison (1994) on the language of drawing, Leal (2011), Bregolato (2007) on the context of the gang, Brikman (1989), Neves (2008), Lobo and Navas (2003) on body.